Optical Biometry versus Ultrasound A-scan in Measuring Anterior Chamber Depth, Axial Length, and Lens Thickness in Patients Undergoing Cataract Surgery - ElNaihom, Esra; Khalifa Elgazzar, (AlQalam Journal of Medical and Applied Sciences, 2024)
Ocular biometry measurements use ultrasonography and optical biometry, offering high precision for noninvasive intraocular distance measurement in cataract surgery. This study aims to Compare agreement values between an optical biometry machine and an ocular ultrasound-based biometry device for axial length, anterior chamber depth, and lens thickness measurements. A study enrolled 64 eyes of 42 patients scheduled for cataract surgery at Benghazi Teaching Eye Hospital, Libya, from January 1st to February 1st, 2024. Patients' medical and ocular histories were taken, and slit lamp examinations were conducted. All eyes with visual impairment and good fixation were included. Axial length, anterior chamber depth, and lens thickness were measured using Aladdin optical biometer and an ellex eye-cubed ultrasonic contact biometer. The study involved 64 eyes with a mean age of 64.36 years, The most common type of cataract was posterior subcapsular cataract [46.9%], nuclear cataract [14.1%], and cortical cataract [14.1%]. Combined cataracts were also present in 31.3% of the participants. The ICC analysis showed a strong agreement [0.976] between the two measurement devices in assessing axial length. difference in measurements of the mean anterior chamber depth. ICC showed a high level of agreement between the two methods [0.545]. There was no significant difference in lens thickness as measured by optical biometry and A-scan ultrasound, with a medium positive correlation between lens thickness measurement by the two devices [P<0.001]. The interclass correlation further supported these findings, with a strong correlation between lens thickness and cataract development [r = 0.753]. The study reveals consistency in the measurements between optical and ultrasound biometry, highlighting the need for future research, to address limitations like small sample size and potential biases. تستخدم القياسات الحيوية للعين عن طريق التصوير بالموجات فوق الصوتية والقياسات الحيوية البصرية، مما يوفر دقة عالية لقياس المسافة داخل العين غير الباضعة في جراحة إعتام عدسية العين. الهدف من هذه الدراسة هو مقارنة قيم الاتفاق بين جهاز القياس الحيوي البصري وجهاز القياس الحيوي المعتمد على الموجات فوق الصوتية للعين لقياسات الطول المحوري، وعمق الغرفة الأمامية، وسمك العدسة .سجلت الدراسة 64 عينًا لـ 42 مريضًا من المقرر لهم إجراء جراحة إزالة المياه البيضاء في مستشفى بنغازي التعليمي للعيون، ليبيا، في الفترة من 1 يناير إلى 1 فبراير 2024. تم أخذ التاريخ الطبي والعيني للمرضى، وتم إجراء فحوصات المصباح الشقي. تم تضمين جميع العيون ذات الإعاقة البصرية والتثبيت الجيد. تم قياس طول المحور وعمق الغرفة الأمامية وسمك العدسة باستخدام مقياس علاء الدين البصري ومقياس الاتصال الحيوي بالموجات فوق الصوتية. شملت الدراسة 64 عينًا بمتوسط عمر 64.36 عامًا، وكان النوع الأكثر شيوعًا لإعتام عدسة العين هو إعتام عدسة العين الخلفي تحت المحفظة (46.9٪)، وإعتام عدسة العين النووي (14.1٪)، وإعتام عدسة العين القشري (14.1٪). كان إعتام عدسة العين المختلط موجودًا أيضًا في 31.3٪ من المشاركين. أظهر تحليل الارتباط داخل الطبقة الاحصائي اتفاقًا قويًا [0.976] بين جهازي القياس في تقييم الطول المحوري. اما بالنسبة لقياسات متوسط عمق الغرفة الأمامية اظهر الارتباط داخل الطبقة مستوى عال من الاتفاق بين الطريقتين (0.545). لم يكن هناك فرق كبير في سمك العدسة كما تم قياسه بواسطة القياسات الحيوية البصرية والموجات فوق الصوتية المسح ، مع وجود علاقة إيجابية متوسطة بين قياس سمك العدسة بواسطة الجهازين [P < 0.001]. دعم الارتباط بين الطبقات هذه النتائج أيضًا، مع وجود علاقة قوية بين سماكة العدسة وتطور إعتام عدسة العين (r = 0.753) تكشف الدراسة عن اتساق في القياسات بين القياسات البصرية والموجات فوق الصوتية، مما يسلط الضوء على الحاجة إلى البحوث المستقبلية ومعالجة القيود مثل حجم العينة الصغير والتحيزات المحتملة